Test and design of built-up stainless steel stub columns - Luqmanul Haziq Kamarudin (Nanyang Technological University, 2022)
An investigation on the ultimate compressive load capacity of 2 configurations of screw-fastened Built-Up Stainless Steel stub column sections is presented in this report. Austenitic stainless steel grade EN 1.4301 plates were first press-braked into C-channels and cut to their desired lengths, before being connected by self-drilling screws to form the 2 cross-sections.